ANALISIS YURIDIS KEKUATAN ALAT BUKTI SAKSI TESTIMONIUM DE AUDITU DALAM SIDANG PERCERAIAN DI PENGADILAN AGAMA KABUPATEN MADIUN - Roihanah, Rif'ah; Cornelia, Irfina (Fakultas Syariah IAIN Ponorogo, 2019)
AbstractA witness is a person who gives testimony before a hearing by meeting certain conditions regarding an event or condition that is seen, experienced, heard itself as evidence of the event or condition. However, what if a witness who appears or is present at a hearing does not see or experience it directly, but hears the incident or situation through news from someone else (testimonium de auditu), while the Religious Court judge may not reject a case that is submitted and brought to him.The formulation of the problem in this study are: How is the juridical analysis of the strength of the evidence of witness testimonium de auditu in divorce cases in the Religious Court of Madiun Regency. And how is the juridical analysis of the judges of the Madiun District Religious Court in divorce cases regarding the use of witness testimonium de auditu.To answer the question above, the researcher used a qualitative approach, looking for data through interviews of the judges as the primary data source, then secondary data was obtained from books that have a connection with this problem. Furthermore, the data obtained were analyzed using a descriptive analysis system. In collecting data using field research techniques and making conclusions (verification). The location of this study was in the Religious Court of Madiun Regency.The results of the study concluded that the strength of the evidence of witness testimonies de auditu in the Religious Court of Madiun Regency according to the juridical study was not appropriate. However, in practice in the courtroom especially in divorce proceedings, the judge has the authority to examine the de auditu witnesses, and there is nothing wrong if the judge hears the testimony of the de auditu witnesses, but the use of de auditu witnesses is not as direct evidence. So de auditu's testimony can be used as a source of allegations. Keywords: Juridical Power, Evidence, Testimonium de Auditu AbstrakSaksi adalah orang yang memberikan keterangan di depan sidang dengan memenuhi syarat-syarat tertentu tentang suatu peristiwa atau keadaan yang dilihat,dialami, didengar sendiri sebagai bukti kejadian atau keadaan tersebut. Namun,bagaimana jika saksi yang muncul atau dihadirkan dalam sidang tidak melihat atau mengalami secara langsung, melainkan mendengar kejadian atau keadaan tersebut melalui kabar dari orang lain (testimonium de auditu), sedangkan hakim Pengadilan Agama tidak boleh menolak perkara yang masuk dan diajukan kepadanya.Rumusan masalah dalam penelitian ini adalah: Bagaimanakah analisis yuridis terhadap kekuatan alat bukti saksi testimonium de auditu dalam perkara perceraian di Pengadilan Agama Kabupaten Madiun. Dan bagaimanakah analisis yuridis terhadap pertimbangan hakim Pengadilan Agama Kabupaten Madiun dalam perkara perceraian tentang penggunaan saksi testimonium de auditu.Untuk menjawab pertanyaan di atas peneliti menggunakan pendekatan kualitatif, dengan mencari data melalui wawancara para hakim sebagai sumber data primer, kemudian data sekunder diperoleh dari buku yang memiliki keterkaitan dengan masalah ini. Selanjutnya data yang diperoleh dianalisis dengan menggunakan sistem deskriptif analisis.Dalam pengumpulan data menggunakan teknik penelitian lapangan (field research) dan pengambilan kesimpulan (verifikasi).Lokasi penelitian ini di Pengadilan Agama Kabupaten Madiun.Hasil penelitian menyimpulkan bahwa Kekuatan alat bukti saksi testimonium de auditu di Pengadilan Agama Kabupaten Madiun menurut kajian yuridis adalah tidak sesuai. Namun, dalam praktik di dalam sidang khususnya dalam siding perceraian, hakim mempunyai wewenang untuk memeriksa saksi de auditu, dan tidak ada salahnya jika hakim mendengarkan keterangan saksi yang de auditu tersebut, akan tetapi penggunaan saksi yang de auditu tidak sebagai bukti langsung. Sehingga kesaksian de auditu dapat dipergunakan sebagai sumber persangkaan.